Kajian Literatur Perbandingan Laboratorium Virtual dan Riil Terhadap Hasil Belajar Kognitif - Khalila Humairo Ramadhani; Nayumi Warta Nabila; Bq. Roswin Tiarti Sari; Gunawan Gunawan; Nina Nisrina (Indonesian Publication Center, 2023)
The development of information and communication technology has driven innovations in learning media, including the use of virtual laboratories as an alternative to real laboratories, which are often limited by facilities. This study aims to analyze and compare the effectiveness of virtual and real laboratories on students’ cognitive learning outcomes. The method used is a literature review by examining 15 relevant journal articles obtained through Publish or Perish connected to Google Scholar. The articles were selected based on relevance and analyzed using content analysis techniques to identify and compare research findings. The results indicate that both types of laboratories contribute to improving cognitive learning outcomes. Real laboratories are superior in providing direct experience, while virtual laboratories are more effective in enhancing motivation, flexibility, and conceptual understanding. Some studies also show no significant difference between the two methods. However, the combination of virtual and real laboratories provides the most optimal results. Therefore, the selection of learning methods should be adjusted to learning needs and conditions to achieve optimal outcomes.